Assessment of dry-matter yield from grain yield in the West African savannah zone - Powell, J.M. (Cambridge University Press, 1984)
A study conducted to test the stability of HI (Harvest Index) relationships for major crops cultivated in West Africa over a range of management levels as an indicator of the quantity of crop residue on offer and to divide the residue of each crop into component plant parts to gain preliminary information on the relative feeding value of total crop resideu dry matter (DM).